Evaluation of health status of Kankrej cattle using mini compton metabolic profile test and correlation with production status - PRAJAPATI, ANKIT; PANCHASARA, HARSHAD; SUTHAR, ABHINAV; CHAUDHARI, ARTH; DEVI, SARITA; PATEL, RAMESHCHANDRA (The Indian Journal of Animal Sciences, 2023)
The present study aimed to assess the changes in metabolite after adaptation of Kankrej breed of cattle from draught to milch purpose. The result showed the resistance power of alteration in metabolic values even after adaptation. Metabolic parameters can be measured to evaluate the health status of individual animal in herd by using mini compton metabolic profile test. Feeding management can be adjusted as per the data of metabolic profile to avoid incidence of metabolic diseases. Indigenous cattle breed is tough enough which resist the alteration in different metabolic parameters.